Políticas de carreiras para o gestor internacional: um estudo em empresas brasileiras internacionalizadas - Domingues, Carlos Roberto (2011)
The objective of this research was identifying which international manager career policies are designed by Brazilian companies and how external and internal factors influence policy designs and which outcomes are achieved. The contextual aspects show Brazil’s economy as an emergent economy, with social and economic indicators in growth which provides an environment for different types of business expansion. The internationalization has been stimulated by Brazilian government and the opportunities arising in the international scenario are levers to the internationalization process of the companies of distinct industries and sizes. So, they demand professionals with capabilities and skills to act and manage an international operation. For theoretical and empirical basis, multinationals companies’ internationalization researches with the economic and strategic approaches were consulted. Also, the researches about international management and change and adjust needed in the structures, activities and controls to perform whole the process of internationalization. In the specific way, it was studied how the Human Resources Management must be structured to attend, through its policies and practices, the companies’ expectations and strategies. The career studies helped to portrait the changes occurred in the work environment and in the individual life expectation as well as to present different models and approaches about career’s types and management. The qualitative approach was chosen and the semi structured interviews and documental analyses were used to collect empirical data. The Human Resources managers of six Brazilian companies collaborated with this research. To help the analysis of collected data, the six companies were divided into three groups: i) the company’s internationalization occurred past ten years or more; ii) the company’s internationalization occurred between ten and five years; and iii) the company’s internationalization occurred at least five years. Observing this criteria, there were choose six companies, two for each group, those that best illustrated or emphasized his group of internationalization, using the sample for a typical case, which seeks to illustrate or highlight what is typical, normal on the average. The resulting research points that the time of internationalization highlights the differences between companies, but he does not explain them all. Some external and internal factors impact on the definitions of policies for managing international career. They are: the level of maturity and competitive markets in which companies operate; the small number of professionals trained to act as international managers in the human resources market; the small number of consultants able to work the issue; the specificity of international profile of the manager; the constant pressure on the international manager; the non linear demand for the position; and organizational culture. Besides these, there is the trust factor, represented both in a moral but also the expectation of completing the work and the decisions that the manager shall, as a representative of the company and its values. In the Group I, the policies for managing international career maturity are the result of the operation of business and the seniority of their HR professionals. Already in the Group II, the design of political career is based on the national operation, enterprise owners and their confidence in the HR field. In companies of the group III, are also characterized by the entrepreneurial spirit of its owners, by its less rigid hierarchical and functional structure, which leads them to have no political career as clear and therefore send their professionals to the outside without much training. In all cases, the level of satisfaction with the outcome is good, however there were concerns expressed and interest in improving the processes. HR professionals are aware that changes will happen before these processes are stabilized. And finally, the recognition by the results is felt at all levels of the organizations, even in the Group III. This satisfaction is measured by the discourse of the owners based on the results obtained so far by international managers.